Analisis Framework Mvc Pada Pengembangan Sistem Penerimaan Siswa Baru - Dedy Armiady (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2021)
The Covid-19 pandemic has changed the behavior and patterns of human life today. The application of health protocols, for example, which changes the conventional work style to a less contact style. The application of the less contact concept during the Covid-19 pandemic implemented an information system that could connect the entities involved and facilitate data management. This study discusses the process of developing information systems, especially web-based information systems which have been built using pure web programming languages ​​such as PHP. This study will also discuss the effectiveness and efficiency of the system development process using the MVC (Model, View and Controller) model. The research method used is an experimental approach with a standard data collection model which includes literature study, interviews, and observation. The system development method used is a prototype development model that is in accordance with the MVC model where the back-end and front-end sides can be done separately. The results obtained from this study are the MVC model used in the process of developing an information system with a case study of developing a new student admissions information system that can be carried out effectively and efficiently